2016
DOI: 10.1186/s13014-016-0712-9
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal melanoma of the head and neck: a population-based study from Slovenia, 1985-2013

Abstract: ObjectivesTo assess the incidence and to review experience with the treatment of mucosal melanoma of the head and neck (MMHN) in Slovenia between 1985 and 2013.MethodsThe National Cancer Registry database and clinical records with outcome data of identified patients treated during the period 1985–2013 in Slovenia were reviewed.ResultsIn a 29-year period, 61 patients with MMHN were identified, representing 0.5 % of all head and neck malignant tumors and 42 % of all mucosal melanomas in Slovenia. 72 % originated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 38 publications
4
25
1
Order By: Relevance
“…As mentioned, there is a range of surgical and radiotherapy techniques that have been employed. 26,27 There is a large degree of heterogeneity in the literature in this regard. We have not given any consideration to the different methodologies that may be employed and have broadly labeled patients as being surgical alone, SRT, or RT, and our analysis does not stratify based on open or endoscopic surgical techniques or based on the dose, fractionation or technique in which RT was administered, which is a limitation of our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, there is a range of surgical and radiotherapy techniques that have been employed. 26,27 There is a large degree of heterogeneity in the literature in this regard. We have not given any consideration to the different methodologies that may be employed and have broadly labeled patients as being surgical alone, SRT, or RT, and our analysis does not stratify based on open or endoscopic surgical techniques or based on the dose, fractionation or technique in which RT was administered, which is a limitation of our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is how we dealt with surgery and radiotherapy as part of our analysis. As mentioned, there is a range of surgical and radiotherapy techniques that have been employed 26,27 . There is a large degree of heterogeneity in the literature in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year OS rate for SNM ranges from 20% to 55% in the literature based on small retrospective cohort studies. 1,27 Amit et al. performed a review of the literature for sinonasal mucosal melanoma which found recurrence rates ranging from 17% to 82.7% and distance metastasis rates as high as 83%.…”
Section: Discussionmentioning
confidence: 99%
“…7 The 5-year OS rate for SNM ranges from 20% to 55% in the literature based on small retrospective cohort studies. 1,27 Amit et al performed a review of the literature for sinonasal mucosal melanoma which found recurrence rates ranging from 17% to 82.7% and distance metastasis rates as high as 83%. [1][2][3]5 The high recurrence rates are thought to be secondary to the multifocal nature of the disease and less associated with lymphatic spread.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, melanoma was regarded as being resistant to conventional RT (7), although this aspect remains controversial. Concerning the treatment of mucosal melanoma, a few studies have reported improved local control (LC) with postoperative RT use (810). However, the role of RT remained limited before the introduction of immune checkpoint inhibitors (ICIs).…”
Section: Introductionmentioning
confidence: 99%